Hospitals’ Legal Responsibility for Service Disruptions due to Information System Failures - Yatno, Yatno; Darmawan, Didit; Khayru, Rafadi Khan (Journal of Social Science Studies, 2023)
The digitization of healthcare services has led hospitals to rely on Hospital Information Systems as the main infrastructure for clinical, administrative and reporting processes. When the system fails and causes service disruptions, questions arise as to how the legal relationship between hospitals and patients can be used to assess possible civil and administrative liability. This study aims to explain the construction of this legal relationship by linking the Hospital Law, Consumer Protection Law, ITE Law, Population Administration Law, as well as Minister of Health Regulations 82/2013 and 88/2015. The method used is a qualitative literature study with a normative juridical approach, based on thematic analysis of legislation and academic literature on health law, consumer protection, and information technology governance. The results of the study show that the legal relationship between hospitals and patients is both contractual and normative. From a contractual dimension, a health service agreement is formed that requires hospitals to provide safe and quality services, including through the management of a reliable information system. From a normative dimension, the Hospital Law and Consumer Protection Law place patients as subjects of rights who are entitled to services in accordance with standards and compensation in the event of losses due to negligence. The Electronic Information and Transactions Law require electronic system operators to maintain the reliability and security of their systems, so that hospitals operating SIRS can be regarded as system operators responsible for losses incurred when the system fails to function properly. In the administrative sphere, Minister of Health Regulation No. 82/2013 requires the implementation of an integrated SIMRS, while Minister of Health Regulation No. 88/2015 regulates the supervision and reporting of hospitals. System failures that disrupt services and reflect violations of these technical provisions can be grounds for administrative sanctions, ranging from warnings to service restrictions. This study concludes that the combination of these regulatory frameworks allows for the imposition of civil liability in the form of compensation to patients, alongside administrative actions by regulators to encourage improvements in the structure and governance of SIRS at the hospital level.